Pengaruh Promosi, Brand Image, Dan Kualitas Produk, Terhadap Keputusan Pembeliam Produk Dabe Beaute di Kota Bekasi - Tamba, Rousdy Safari; Gumilar, Elfa Satria (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of promotion, brand image, and product quality on the purchase decision of Dabe Beaute beauty products in Bekasi City. Research methods based on the philosophy of positivism, used to research on certain populations or samples, data collection using research instruments, data analysis is quantitative or statistical with the aim of testing predetermined hypotheses. The method I used in this study uses quantitative methods in the form of numbers and statistical methods. This data collection technique uses the Accidental Sampling Technique. Accidental sampling is a way of sampling based on convenience. In this study, the sampling used the formula according to Hair et al (2010). The sample in this study were 210 Dabe Beaute consumer respondents. The results of this study indicate that Promotion has a positive effect on Purchasing Decisions by 28.9%. Brand Image has a positive effect on Purchasing Decisions by 04.2%. Product Quality has a positive effect on Purchasing Decisions by 30.5%. Promotion, Brand Image, and Product Quality have a positive effect on Purchasing Decisions by 31.3%, while the remaining 68.7% is influenced by other factors not examined in this study.